E-Mental Health: A Qualitative Study of Telepsychology’s Role in Mental Health Accessibility and Help-Seeking Behaviors - Galing, Viell Antoinette (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the role of telepsychology in mental health accessibility and help-seeking behaviors among telepsychology users and mental health service providers in the Philippines. Anchored on the increasing demand for accessible mental health services and the integration of digital technology in psychological care, the study utilized the Consensual Qualitative Research (CQR) approach to examine participants lived experiences regarding telepsychology. Data were gathered through semi-structured interviews involving eight (8) participants, composed of four (4) telepsychology users and four (4) mental health service providers. The study identified six major domains: Perceptions and Experiences of Telepsychology, Accessibility of Telepsychology Services, Barriers to Telepsychology, Influence on Help-Seeking Behaviors, Technological and Psychological Factors Affecting Use, and Recommendations for Improving Telepsychology. Findings revealed that telepsychology improved access to mental health services by reducing geographical, financial, and logistical barriers while promoting flexibility, convenience, and continuity of care. Participants also reported increased willingness to seek professional help due to familiarity with digital platforms, relative anonymity, and ease of access. However, challenges such as unstable internet connectivity, privacy concerns, technological disruptions, reduced nonverbal communication, and limitations in behavioral observation affected service delivery and therapeutic engagement. Despite these challenges, participants perceived telepsychology as a viable, ethical, and sustainable approach to mental health care. The study further recommended strengthening digital infrastructure, improving clinician training, developing secure platforms, and establishing standardized protocols to enhance the quality and sustainability of telepsychology services. The study supports Sustainable Development Goal (SDG) 3: Good Health and Well-Being by promoting accessible mental health services through digital platforms. It also aligns with SDG 10: Reduced Inequalities by addressing barriers experienced by individuals in remote and underserved communities. The sustainability impact of the study lies in its contribution to improving long-term access to mental health services through technology-based interventions. The findings support the development of sustainable and inclusive mental health care systems that can strengthen institutional practices, service continuity, and community well-being.